2015 IEEE 16th International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM) 2015
DOI: 10.1109/wowmom.2015.7158194
|View full text |Cite
|
Sign up to set email alerts
|

Unified approach for performance analysis of Cognitive Radio Spectrum Sensing over correlated multipath fading channels

Abstract: In this work, we analyse the performance of Cognitive Radio Spectrum Sensing (CRSS) systems with multiple receiving antennas considering the effect of correlation among fading branches. Exact closed-form expressions for the average detection probabilities (P D ) are derived employing Probability Density Functions (PDF) approach for n.i.i.d.-L number of diversity branches over Nakagami-m fading channels with Maximal Ratio Combining (MRC) diversity. Performance analysis reveals the detrimental effect of the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The higher the number of tapers, the more processing burdens unnecessarily invoked and, hence, practically meaningful values need to be managed. One of the essential evaluation tools is the receiver operation characteristic (ROC) curve, which governs the two probabilities given in (22) and (24). Since the ROC curve shows the achieved as a function of the , it exposes the general performance for a particular detector.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the number of tapers, the more processing burdens unnecessarily invoked and, hence, practically meaningful values need to be managed. One of the essential evaluation tools is the receiver operation characteristic (ROC) curve, which governs the two probabilities given in (22) and (24). Since the ROC curve shows the achieved as a function of the , it exposes the general performance for a particular detector.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Among several recent studies in this regard, one particularly interesting investigation [22] showed that fading, such as Nakagami type, can cause harmful correlation between channels and this will degrade the detection process. Therefore, a mitigation approach employing diversity techniques, especially MRC, was suggested to alleviate such fading effects and eventually render the SE performance more robust against noise uncertainty [13,22]. An alternative remedy of fading is by exploiting multicarrier (MC) or multitoned (MT) transmission features.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work [17], we extended the investigations in [15] by deriving exact closed-form expressions for constant and exponentially correlated L-antenna branches in Nakagami-m channel for MRC diversity technique.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in order to gain an insight into the derived expressions, numerical evaluations are done for both MRC and EGC diversity solutions. We consider SNR values and fading severities that are different than those considered in [17]. Numerical results show that the inter-branch correlation impacts the detector performance significantly.…”
Section: Introductionmentioning
confidence: 99%
“….17)Now, by choosing appropriate parameter values to satisfy the condition within, the solution of (3.15) is[78,79] …”
mentioning
confidence: 99%